(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Pesticide residues in or on food commodities is the major concern towards the food safety. Today’s era characterized by the tremendous application of chemical pesticides in agricultural field. Present study were conducted in Jalgaon district to assess the overall use of pesticide for agriculture purposes. This study includes the survey of pesticide sellers by considering different aspects in questionnaire regarding the use and sell of pesticides throughout the district. Total 40 pesticide sellers were interviewed to evaluate the awareness level and knowledge about safe use of pesticides. The study has found that 59% of sellers did not receive any type of training regarding safe use of pesticides. 63% of sellers were aware about required dose of pesticide and its preparation for spraying on crops.